The pivotal role of MBD4–ATP7B in the human Cu(i) excretion path as revealed by EPR experiments and all-atom simulations. Issue 7 (12th June 2019) - Qasem, Zena; Pavlin, Matic; Ritacco, Ida; Gevorkyan-Airapetov, Lada; Magistrato, Alessandra; Ruthstein, Sharon
Abstract : Atox1–MBD4 interaction mediates the in-cell Cu(i ) concentration. Abstract : Copper's essentiality and toxicity require a meticulous mechanism for its acquisition, cellular distribution and excretion, which remains hitherto elusive. Herein, we jointly employed electron paramagnetic resonance spectroscopy and all-atom simulations to resolve the copper trafficking mechanism in humans considering the route travelled by Cu(i ) from the metallochaperone Atox1 to the metal binding domains 3 and 4 of ATP7B. Our study shows that Cu(i ) in the final part of its extraction pathway is most likely mediated by binding of Atox1 monomer to MBD4 of ATP7B. This interaction takes place through weak metal-stabilized protein–protein interactions.